Simulation of an Automated System with Hardware in the Loop Using a Human Machine Interface (HMI) for the Process of Bottling Liquids Employing Unity 3D - Rivas, Fabián (2024)
This document shows the development of the simulation of an automated bottle filling and sealing system in order to monitor and supervise the behavior of each stage of the process using the Unity 3D software. In addition, the implementation the Modbus RTU network, which will be communicated to the PLC, applying Ladder programming through the Tia Portal V17 software, in order to determine the states of the input and output variables, as well as the behavior that occurs in the event of failures. In addition, the use of hardware in the loop that through an HMI system which allows us to establish the desired communication with the Unity 3D software, knowing the process of bottling and sealing bottles that is very common in the industry.